a. First, turn the left side of the equation into a single fraction, by using a common denominator.
1/3 - 5/6 = (2-5)/6 = -3/6 = -1/2
That leaves you with
-1/2 = 1/x
-x = 2
x = ?
b. t + 1/3 -t -1/2 = 1
has no solution, because the t terms cancel out, leaving you with a false statement.
You probably meant to write
(t+1)/3 - (t-1)/2 = 1
That does have a solution. Again, form a common denominator
[2(t+1) - 3(t-1)]/6 = 1
(-t +5)/6 = 1
Multiply both sides by 6 and combine constant terms.
-t + 5 = 6
-t = 1
t = ?
Please solve:
a. 1/3 - 5/6 = 1/x
b. t+1/3 - t-1/2 = 1
2 answers
12,4